“It Doesn’t Feel Like a Natural Fit”: Co-operating Teachers Account for Their Evaluation and Assessment of Pre-service Teachers’ Efforts to Fulfill Social Justice Indicators - Mulholland, Valerie Lyn; Salm, Twyla (Alberta Journal of Educational Research, 2017)
Teacher education has long been troubled by the problem of reconciling what happens in course work with how that learning is taken up in practicum experiences. Our faculty asks co-operating teachers to account for interns’ professional growth by the extent to which the interns meet the requirements of the Internship Placement Profile (IPP). The study focuses on the eight IPP items which relate directly to “teaching for social justice.” The theoretical framework draws upon the literature of anti-oppressive/anti-racist pedagogies. Co-operating teachers and interns are expected to rely on the field manual that lists descriptors for each item of the IPP to assess growth and to set goals. The objective to understand how co-operating teachers perceive their intern’s ability to teach for social justice and reach their final evaluation was modified to reflect the finding that cooperating teachers were sometimes less familiar with these principles than were the interns. La formation des enseignants a depuis longtemps été affectée par le problème qui consiste à concilier le travail en classe et l’application de cet apprentissage pendant les stages. Notre faculté demande aux enseignants coopérants de rendre compte du développement professionnel des stagiaires en notant la mesure dans laquelle ceux-ci répondent aux exigences du profil du stage (Internship Placement Profile -IPP). Cette étude porte sur les huit items du IPP qui touchent directement l’enseignement qui vise la justice sociale. Le cadre théorique puise dans la littérature des pédagogies anti-oppressives/anti-racistes. L’on s’attend à ce que les enseignants coopérants et les stagiaires évaluent la croissance et fixent des objectifs en s’appuyant sur le manuel qui contient la liste de descripteurs pour chaque item du IPP. L’objectif touchant l’évaluation par les enseignants coopérants de la capacité des stagiaires d’enseigner la justice sociale a été modifié de sorte à tenir compte de la constatation que les enseignants coopérants connaissaient parfois moins bien ces principes que les stagiaires.